Supply Chain Analysis of Tofu Products in The FR Tofu Agroindustry Sepande Village - Linda Octavia Kusumawardhani; Taufik Setyadi; Risqi Firdaus Setiawan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
A supply chain is a network of companies that work together to make and deliver products to end consumers. Specific market segments consume agricultural products and have a supply chain structure consisting of individuals based on trust between actors. Most companies in Indonesia have implemented supply chain management, but many have not maximized it, so it runs less effectively and efficiently. The problem in the FR tofu agroindustry is the incompatibility of the delivery schedule of soybean raw materials. This is due to climate change, poor weather conditions, and trade policies between countries that impact imported soybean production, which will hamper the production process in the FR tofu agroindustry. This study analyzes the supply chain flow of tofu products in the FR tofu agroindustry. The research was conducted at the FR tofu agroindustry in Sepande Village, Candi District, Sidoarjo Regency, from February to March 2024. The analytical method used in this research is descriptive qualitative analysis. This study's informants were six: 1 owner of FR tofu agroindustry, two people in tofu production, one soybean supplier, one cooperative employee, and one tofu retailer trader. The results showed that the supply chain flow of tofu products in the FR tofu agroindustry consisted of three flows, namely the flow of product (upstream to downstream), the flow of financial (downstream to upstream), and the flow of information (upstream to downstream and vice versa) The parties involved in the supply chain of tofu products are CV Rahardjo Indobeans, KOPTI "Karya Mulya" FR tofu agroindustry, and retail traders. This research suggests that the FR tofu agroindustry needs to build stronger relationships with local and imported soybean suppliers.